Single Burr Hole Craniostomy in surgical treatment of chronic subdural hematoma (Outcome and Complications) - AbdulWahid, Ali T. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: There is controversy among neurosurgeons whether double Burr Hole craniostomy is better than single Burr Hole, craniostomy in the management of chronic subdural hematoma in terms of lower recurrence rate and complications.Objective: To assess the outcome and complications including revision rate using Single Burr Hole Craniostomy in the treatment of chronic subdural hematoma (CSDH).Patients and Methods: This is a retrospective study of 42 cases of chronic subdural hematoma who underwent Single Burr Hole Craniostomy(SBHC) from jan.2012 to jan.2014, preoperative,intraoperative and postoperative data were collected including neurological status ,Brain CT-scan findings, postoperative complications ,recurrent rate and neurological deficit.Results: Forty two patients (36 male and 6 female, with age ranged between 60y.-82y.) were treated by Single Burr Hole Craniostomy for chronic subdural hematoma. There were two recurrences, one stroke, and one death after primary surgery. The two recurrent cases were treated by drainage through same Burr Hole and both they did well (recovered uneventfully).Conclusions: The results of this study suggest that Single Burr Hole Craniostomy is safe, simple and effective method for surgical management of CSDH with lower recurrence rate and lower morbidity and mortality.